The Sarbanes-Oxley Act, Earnings Management, and Post-Buyback Performance of Open-Market Repurchasing Firms - Chen, Sheng-Syan; Huang, Chia-Wei (Journal of Financial and Quantitative Analysis, 2013)
We examine how the Sarbanes-Oxley Act (SOX) affects pre-repurchase earnings management and its association with post-repurchase firm performance. Unlike prior pre-SOX studies, our post-SOX results indicate that open-market repurchasers do not engage in pre-buyback downward accrual-based earnings management. Audit committee independence, reforms in corporate governance structures, and changes in executives’ equity holdings prompted by SOX may explain the findings. Post-SOX, the significant negative association between pre-repurchase abnormal accruals and post-repurchase performance disappears, the market reaction to repurchase announcements becomes significantly less favorable, and there is no evidence of any shift away from accrual-based to real earnings management.